1985
DOI: 10.1016/s0022-5347(17)47709-3
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Retention Induced by Estrogen Injections in Mice: An Analytical Model

Abstract: Daily subcutaneous injections of pharmacological doses of 17 beta-estradiol (E2, 0.4 micrograms./gm. body weight) resulted in significant urinary retention in the bladder of castrated mice. Although the urinary retention developed in both male and female mice, the increase in urethral resistance to urinary flow and the dilatation of posterior urethra were observed only in castrated male mice receiving E2. Histological changes common to male and female mice were cornification and stratification of urethral epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…In both male and female gonadectomized DS (mutation disorganization) strain mice exposed to 17b-estradiol, significant urine retention and 100% hydronephrosis were observed. 7 An additional study found that 17b-estradiol treatment administered via subcutaneous pellets caused hydronephrosis and urine retention in female C57BL/6J mice. 8 The results observed in lab animals seem to be contradictory to the studies conducted in humans, possibly because of a different dose regimen of estrogen in lab animals and because postmenopausal women are deprived of estrogen for a very long time, which could trigger many pathways.…”
Section: Introductionmentioning
confidence: 99%
“…In both male and female gonadectomized DS (mutation disorganization) strain mice exposed to 17b-estradiol, significant urine retention and 100% hydronephrosis were observed. 7 An additional study found that 17b-estradiol treatment administered via subcutaneous pellets caused hydronephrosis and urine retention in female C57BL/6J mice. 8 The results observed in lab animals seem to be contradictory to the studies conducted in humans, possibly because of a different dose regimen of estrogen in lab animals and because postmenopausal women are deprived of estrogen for a very long time, which could trigger many pathways.…”
Section: Introductionmentioning
confidence: 99%
“…This interaction has been noted to induce significant bladder distention in mice (Kuroda et al. ). As such, the close anatomical proximity of the urinary bladder to the hind limbs could speculatively alter the mechanics of running during estrogen treatment, and therefore, satisfactorily explain the lackluster recovery observed during short‐term estrogen treatment and manipulation.…”
Section: Discussionmentioning
confidence: 91%
“…The retention of urine as a byproduct of estrogen treatment is well established in the scientific literature (Kuroda et al. ; Kuiper et al. ; Levin‐Allerhand et al.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although not reviewed by Osman and Chapple, 1 evidence suggests that oestrogens could increase detrusor and u rethral p ressure and cause urinary retention. [4][5][6][7] Kuroda et al 4 reported that oestradiol injections resulted in urinary retention CORRESPONDENCE Fowler's syndrome-progesterone deficiency or oestrogen excess? Jae I. Shin in the bladders of castrated mice, and Bump and Friedman 5 showed that oestradiol replacement in hypo-oestrogenic baboons increased functional urethral length and mean urethral pressure.…”
mentioning
confidence: 99%